Multisensory Imaginings: An Audionarratological Analysis of Philip Roth's Novel Indignation and its German Radio Play Adaptation Empörung. Issue 3 (December 2016) - Mildorf, Jarmila; Kinzel, Till
Abstract : This article analyses the German radio play adaptation of Philip Roth's novel Indignation ( Empörung, 2010) from an audionarratological perspective and shows how both the book and the radio play offer potential for multisensory experiences on the part of readers and radio audiences. The article furthermore explores how the two media differ in their semiotic and sensory affordances and possibilities. It is argued that aural signs and signals predetermine certain aspects of the storyworld in the radio play: for example, characters' and the narrator's voices, soundscapes, but also ambient sound and music. Due to its focus on the aural channel, radio drama calls on audiences' imagination in distinct ways, while also complicating narratological concepts. The 'transcriptivity' from written to spoken text that is inherent in the transposition of novel into radio play accounts for the fact that the radio play also adds new multisensory and interpretive dimensions to its pre-text. It therefore has to be considered in its own right, as an artistic form appealing to its audiences through its own sensory channels.